Structures of the genes for the β and ε subunits of spinach chloroplast ATPase indicate a dicistronic mRNA and an overlapping translation stop/start signal - Zurawski, Gerard (1982)
A 2,4-kilobase-pair region of spinach chloroplast DNA adjacent to the gene for the large subunit of ribulosebisphosphate carboxylase has been analyzed by RNA hybridization, in vitro transcription/translation, and DNA sequence determination. The analysis indicates that this region carries the genes for the β and ε subunits of chloroplast ATPase and that the two genes are cotranscribed into a dicistronic mRNA with 4-base-pair overlap between the stop codon of the β-subunit gene and the start codon of the ε-subunit gene. The ATPase and carboxylase genes are transcribed divergently with respect to each other. The deduced amino acid sequences of the β and ε subunits from spinach show 67% and 26% homology, respectively, with the published sequences of the β and ε subunits of Escherichia coli ATPase.